2022
DOI: 10.1186/s12886-022-02450-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the biometric parameters in patients with high myopia and anisometropia

Abstract: Background To compare biometric parameters, especially lens parameters, in patients with high myopia and anisometropia. Methods Patients with spherical equivalent greater than -6D and at least one eye with an axial length greater than 26 mm and a difference in binocular axial length greater than 2 mm were included in this study. In each patient, the eye with a relatively shorter axial length was assigned to Group S, and the other eye was assigned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Consequently, the correlation with AL diminishes ( Liu et al, 2021 ; Sedaghat et al, 2021 ). Liu et al ( Liu J. et al, 2022 ) observed no significant differences in ACD, CCT, Km, and LT among highly myopic eyes with anisometropia. Furthermore, Liu et al ( Liu et al, 2021 ) reported a lack of significant correlation between SSI and AL in eyes with severe axial elongation (AL≥26 mm), suggesting a non-linear influence of AL on corneal parameters.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Consequently, the correlation with AL diminishes ( Liu et al, 2021 ; Sedaghat et al, 2021 ). Liu et al ( Liu J. et al, 2022 ) observed no significant differences in ACD, CCT, Km, and LT among highly myopic eyes with anisometropia. Furthermore, Liu et al ( Liu et al, 2021 ) reported a lack of significant correlation between SSI and AL in eyes with severe axial elongation (AL≥26 mm), suggesting a non-linear influence of AL on corneal parameters.…”
Section: Discussionmentioning
confidence: 97%
“…It is important to note that AL elongation tends to be relatively uniform during the physiological progression of myopia. However, in cases of pathological myopia, the extension is primarily concentrated at the posterior pole, with anterior structural changes remaining relatively stable ( Liu J. et al, 2022 ). Consequently, the correlation with AL diminishes ( Liu et al, 2021 ; Sedaghat et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The rapid increase in the myopia population has become a global public health problem [1] . High myopia is usually defined as spherical refractive errors less than -6.00 diopters (D) or ocular axial length (AL) more than 26 mm [2] . Elongation of the AL and thinning of the retina, which often cause a series of degenerative changes in the fundus of pathological myopia, such as fundus tessellation (FT), temporal peripapillary chorioretinal atrophy, posterior scleral staphyloma, lacquer crack, myopic retinoschisis, and macular degeneration, is one of the common causes of blindness in China [3][4] .…”
Section: Introductionmentioning
confidence: 99%